Mata Air dan Kelimpahan Vegetasi Pada Taman Wisata Alam Gunung Meja Kabupaten Manokwari - Mahmud, Mahmud; Rahmanto, Syaiful; Kesaulija, Francina F.; Muhlis, La Ode (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Water is a vital need for every life, so if there is no water there will certainly be no life. This research aims to determine the pattern of springs, diversity and similarity of types around the springs. The research method uses surveys and sampling techniques. Research results of Meja Mountain Natural Tourism Park (MMNTP) from 9 springs have 7 different spring patterns. The largest water discharge in the spring pattern that comes out between the rocks, while the smallest water comes out of seepage of soil pores. The largest water discharge is located in Manggoapi with coordinates -0.847744, 134.069008. While the smallest water discharge comes from springs that emerge from the ground located in Brawijaya with coordinates -0.854717, 134.075233. The woody vegetation type diversity index has a high value which reflects the diversity of types in the MMNTP. Meanwhile, the similarity index is higher than the difference, indicating that woody vegetation has similarities between the observation plots. Establish from seedlings to dominant trees including Palaquium amboinensis, Artocarpus altilis, Lansium domesticum, Pometia coriacea, Pometia pinnata, and Koordersiodendron pinnatum. The six types are thought to have suitable habitats, need lots of water and have related relationships.